Masalah Pertahanan: Redefinisi dan Agenda Aksi - Jahja A. Muhaimin (Jurnal Ilmu Sosial dan Ilmu Politik, 2002)
As international politics is changing along the line of globalization, new issues are emerging and new approach is required. Nonetheless Indonesia has been insensitive to such imperative as public attention has been devoted to much on domestic political reform. This article suggests that epistemic community on defense issue shall take pivotal part in dealing with defense policy.